1994
DOI: 10.3109/08910609409141570
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplements with Bifidobacterium longum and Lactobacillus acidophilus on the Intestinal Microbiota during Administration of Clindamycin

Abstract: Thirty healthy volunteers in three groups participated in a study of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 28 publications
3
37
0
2
Order By: Relevance
“…Previous studies have shown (10,19,24) that clindamycin has a great effect on the anaerobic community. In one of these studies (24), alterations of the fecal microflora in 24 healthy subjects who received clindamycin for 1 week, with or without a probiotic containing two Lactobacillus strains and one Bifidobacterium strain, were monitored by cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown (10,19,24) that clindamycin has a great effect on the anaerobic community. In one of these studies (24), alterations of the fecal microflora in 24 healthy subjects who received clindamycin for 1 week, with or without a probiotic containing two Lactobacillus strains and one Bifidobacterium strain, were monitored by cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…Several health benefits have been ascribed to bifidobacteria, including reduction of blood cholesterol (Molder, 1994), improving lactose utilization in malabsorbers (Jiang, Mustapha & Savaiano, 1996), deconjugation of bile acids (Lankaputhra & Shah, 1995) and increasing immunity in host animals (Simone et al, 1992). In addition, bifidobacteria have been shown to help maintain a healthy microbial equilibrium in the gastrointestinal tract, thereby reducing the incidence of traveler's diarrhea and antibiotic-associated diarrhea (Orrhage, Brismar & Nord, 1994). This has reinforced their status as probiotic bacteria and led to their increased use in fermented food products and pharmaceutical preparations.…”
Section: Introductionmentioning
confidence: 98%
“…Such 'probiotics', defined as living microorganisms, which upon ingestion in certain numbers, exert health affects beyond inherent basic nutrition (2), have been assessed in human disorders such as small bowel bacterial overgrowth (3), colorectal cancer (4), diarrhoea in children (5), traveller's diarrhoea (6) and antibiotic/ Clostridium difficile -associated diarrhoea (7,8).…”
Section: Introductionmentioning
confidence: 99%